1994
DOI: 10.1113/jphysiol.1994.sp020205
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐conotoxin‐sensitive and ‐resistant transmitter release from the chick ciliary presynaptic terminal.

Abstract: 7. Similarly, the EPSC was smaller in the 10 mm Ca2+-l mm K+ solution containing 5 /uM La3+ than in the 2 mm Ca2+-16 mM Mg2+ solution, whereas the A[Ca2+]pre was larger in the 10 mM Ca2+-1 mm K+ solution containing 5/M Li3+ than in the 2 mm Ca2'-16 mM Mg2+ solution. 8. It is concluded that the w-CgTX-sensitive Ca21 conductance of the presynaptic terminal is the principal source of Ca2" involved in transmitter release. Although the w0-CgTXresistant conductance which is inactivated at depolarized membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…The involvement of N-type Ca 2+ channels in synaptic transmission in our preparation is indicated by the irreversible reduction of the EPSC and IPSC amplitudes by ~-CTx GVIA. This is in line with observations in several other preparations [6,13,19,22,29,40,55,58,60] and supported by biochemical data suggesting a very close association of N-type Ca 2+ channels with syntaxin and synaptotagmin [8, 26, 37, 45, 591. glutamatergic as well as of GABAergic neurons, or that Ca 2+ influx through L-type Ca 2+ channels occurs at a site remote from transmitter release. Evidence for a presynaptic lack of L-type Ca 2+ channels comes from immunohistochemical studies [1,17] and from recent investigations using Ca 2+ imaging techniques which have shown that Ca 2+ influx through L-type Ca 2+ channels is mainly restricted to the soma [20].…”
Section: Ca 2+ Channels Contributing To Excitatory and Inhibitory Synsupporting
confidence: 91%
“…The involvement of N-type Ca 2+ channels in synaptic transmission in our preparation is indicated by the irreversible reduction of the EPSC and IPSC amplitudes by ~-CTx GVIA. This is in line with observations in several other preparations [6,13,19,22,29,40,55,58,60] and supported by biochemical data suggesting a very close association of N-type Ca 2+ channels with syntaxin and synaptotagmin [8, 26, 37, 45, 591. glutamatergic as well as of GABAergic neurons, or that Ca 2+ influx through L-type Ca 2+ channels occurs at a site remote from transmitter release. Evidence for a presynaptic lack of L-type Ca 2+ channels comes from immunohistochemical studies [1,17] and from recent investigations using Ca 2+ imaging techniques which have shown that Ca 2+ influx through L-type Ca 2+ channels is mainly restricted to the soma [20].…”
Section: Ca 2+ Channels Contributing To Excitatory and Inhibitory Synsupporting
confidence: 91%
“…Whether such small differences in Ä [Ca¥]v are sufficient to account for the large differences in the probability for secretion from the varicosities, given the non-linear relationship between calcium and transmitter release at these varicosities (Macleod et al 1994), remains to be determined. It is of interest to observe the amplitude of the Ä [Ca¥] in terminals in order of decreasing size: 10-20 nÒ in the calyciform terminal of the avian ciliary ganglion (Yawo & Chuhma, 1994;2 ² 20 ² 20 ìmÅ), approximately 30 nÒ in the hippocampal to CA3 pyramidal cell synapse (Regehr, Delaney & Tank, 1994; 3-5 ìm diameter), 65 ± 12 nÒ in the sympathetic varicosities of the mouse vas deferens (this paper; 1·36 ± 0·21 ìm diameter) and approximately 300 nÒ at the cerebellar granule cell to Purkinje cell synapse (Regehr & Atluri, 1995; < 1 ìm diameter). The inverse relationship between the size of the terminal and the amplitude of response to single action potentials suggests that these differences are due to differences in the surface area to volume ratio of the terminals, although other factors such as calcium conductivity differences, differences in the extent of calcium dumping by intracellular stores, or decreased intracellular buffering in the sympathetic postganglionic terminals, may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Patch-clamp recording from neurons in intact ganglia was performed as described previously (Yawo and Chuhma, 1994;Z hang et al, 1996). Patch pipettes (2-3 M⍀) were pulled from borosilicate glass (1.5 mm outer diameter, Drummond Scientific, Broomall, PA).…”
Section: Methodsmentioning
confidence: 99%